1967
DOI: 10.1113/expphysiol.1967.sp001909
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Hydrogen Sulphide and Other Sulphides

Abstract: 1. Hydrogen sulphide inhaled, or sulphide or H,S injected in solution into the circulation, is carried for a time in the plasma in the form of an equilibrium mixture of sulphide and H2S. It only slowly penetrates into the red cells, where it is destroyed in reactions in which oxyhaemoglobin is reduced. The lethal dose of H2S will therefore vary according to the rate and site of its administration.2. The physiological effects of hydrogen sulphide and other sulphides are similar to those of hydrocyanic acid, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 7 publications
2
109
1
Order By: Relevance
“…Hydrogen sulfide (H2S) is a toxic gas that inhibits enzyme systems in animals (91), and a single inhalation of 1,800 ppm can produce death in mammals (dog and humans) (92). Inhaling 500-1,500 ppm for long periods can lead to respiratory failure and death (93)(94)(95) …”
Section: Avian Respiratory Toxicology Inhaled Particulatesmentioning
confidence: 99%
“…Hydrogen sulfide (H2S) is a toxic gas that inhibits enzyme systems in animals (91), and a single inhalation of 1,800 ppm can produce death in mammals (dog and humans) (92). Inhaling 500-1,500 ppm for long periods can lead to respiratory failure and death (93)(94)(95) …”
Section: Avian Respiratory Toxicology Inhaled Particulatesmentioning
confidence: 99%
“…The inhibitory effects of sulfide on respiration are reversible once sulfide dissipates or is chemically oxidized (Evans 1967). Results from the present study indicate that sulfide is most probably removed from the burrow environment by ventilation processes.…”
Section: Discussionmentioning
confidence: 51%
“…The discrepancy between the ventilation patterns obtained during sulfide exposure in this study and those observed by Kristensen (1983a) during hypoxia probably illustrated toxic effects of HS-, particularly at high concentrations. Toxicity to sulfide results from the blockage of the respiratory electron transport chain (Torrans & Clemens 1982) which in turn inhibits key enzymes (Evans 1967). The pronounced rightsided tail of the HS-efflux curve especially for N. virens (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'^'^ Swine exposed to 1000 ppm H^S, can recover immediately upon termination of the gas, and appear clinically normal.^®® Torrans and Clemens^'^^ reported that catfish cytochrome oxidase activity inhibited 50% of normal returned to control levels in six hours. Cows continuously exposed for three weeks at 20 ppm did not develop alterations in heart rate, feed Table Nervous system Fatalities associated with hydrogen sulfide are generally due to irreversible cellular changes in the nervous system that result in acute respiratory paralysis., 74,96,253,268 Depression of cytochrome oxidase has long been considered the mechanism of systemic toxicosis, although alternate or additional routes causing respiratory distress have recently been proposed. At <200 ppm the gas depresses the central nervous system, >200 ppm can stimulate the CMS, and >700 ppm results in paralysis (Table 5) Reduced capacity for potential conduction is suggested.…”
Section: Chronicmentioning
confidence: 99%